2001
DOI: 10.1090/conm/280/04630
|View full text |Cite
|
Sign up to set email alerts
|

A survey of model reduction methods for large-scale systems

Abstract: An overview of model reduction methods and a comparison of the resulting algorithms is presented. These approaches are divided into two broad categories, namely SVD based and moment matching based methods. It turns out that the approximation error in the former case behaves better globally in frequency while in the latter case the local behavior is better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
435
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(443 citation statements)
references
References 21 publications
1
435
0
7
Order By: Relevance
“…Most general purpose model reduction techniques can be classified into either singular value decomposition (SVD) or Krylov-based methods. Research work relating to such concepts can be found in (Antoulas, et al, 2001;Gugercin and Antoulas, 2004;Antoulas, 2005) as a series of recent surveys.…”
Section: Model Reduction Methodsmentioning
confidence: 99%
“…Most general purpose model reduction techniques can be classified into either singular value decomposition (SVD) or Krylov-based methods. Research work relating to such concepts can be found in (Antoulas, et al, 2001;Gugercin and Antoulas, 2004;Antoulas, 2005) as a series of recent surveys.…”
Section: Model Reduction Methodsmentioning
confidence: 99%
“…The matrices here do not necessarily have anything to do with the transfer function. Consider 1) where N 1 + N 2 = N . The following theorem describes the structures in a basis matrix of K k (A, B) when one of A ij 's is zero.…”
Section: Structures Of Krylov Subspaces Of Block Matricesmentioning
confidence: 99%
“…Recent survey articles [1,2,7] provide in depth review of the subject and comprehensive references. Roughly speaking, these methods project the original system onto a smaller subspace to arrive at a (much) smaller system having properties, among others, that many leading terms (called moments) of the associated (matrix-valued) transfer functions expanded at given points for the original and reduced systems match.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many existing model reduction methods such as balanced truncation and Hankel norm approximations [2,39], Krylov projection methods, and in particular the Arnoldi and Lanczos algorithms [4,7,26,27,36], exploit the sparsity of the large scale model and have been extensively used for model reduction of large scale systems; see [3,8,36] and the references therein. In these approaches, G m (s) is computed such that it matches the moments of G(s), that is the value of G(s) and its derivatives, at certain interpolation points.…”
Section: Introductionmentioning
confidence: 99%